Employer’s perception on graduates soft skills,employability/ Azhar Suleiman - Suleiman, Azhar (2012)
Over the past 20 years organisations have been increasingly influenced by the forces of internationalisation and globalisation. Hence, universities across the globe including Malaysia increasingly required to produce highly skilled graduates who are able to respond to the ever changing and complex needs of the contemporary workplace in term of employment (Weil, 1999; Sleezer et al., 2004; Possa, 2006). Graduates are not only evaluated interm of their academic performance but skills and working experiece are required in order for them to be employable and marketable.